Health at Every Size®-Based Interventions May Improve Cardiometabolic Risk and Quality of Life Even in the Absence of Weight Loss: An Ancillary, Exploratory Analysis of the Health and Wellness in Obesity Study - Dimitrov Ulian, Mariana; Pinto, Ana Jéssica; Morais Sato, Priscila de; Benatti, Fabiana B.; Lopes de Campos-Ferraz, Patricia; Coelho, Desire; Roble, Odilon J.; Sabatini, Fernanda; Perez, Isabel; Aburad, Luiz; Vessoni, André; Fernandez Unsain, Ramiro; et al. (Frontiers in Nutrition, 2022)
We examined whether weight loss following HAES®-based interventions associates with changes in cardiometabolic risk factors and quality of life of women with obesity. This was an exploratory, ancillary analysis of a seven-month, mixed-method, randomized controlled trial. Fifty-five women (age: 33.0±7.2; BMI: 30-39.9 kg/m2) were included in this study. Body weight, cardiovascular risk factors, clustered cardiometabolic risk, and quality of life were assessed before (Pre) and after HAES®-based interventions (Post). Delta scores (Post-Pre) were calculated for each outcome and used in linear regression models. After adjusting by potential confounders, weight loss was associated with improvements in waist circumference (β=0.83, p<0.001), fasting glycemia (β=0.45, p=0.036), total cholesterol (β=1.48, p=0.024), LDL (β=1.33, p=0.012), clustered cardiometabolic risk (β=0.18, p=0.006), and quality of life (β=-1.05, p=0.007). All participants but one who reduced body weight (n=11) improved clustered cardiometabolic risk and quality of life. Of relevance, 34% and 73% of the participants who maintained or gained weight improved clustered cardiometabolic risk and quality of life, respectively, although the magnitude of improvements was lower than that among those who lose weight. Improvements in cardiovascular risk factors and quality of life following HAES®-based interventions associated with weight loss as expected. However, most of the participants who maintained or even gained weight experienced benefits to some extent. This suggests that weight-neutral, lifestyle-modification interventions may improve wellness and health-related outcomes, even in the absence of weight loss.